2022
DOI: 10.1039/d1nj06124k
|View full text |Cite
|
Sign up to set email alerts
|

Amine-functionalized MCM-41 as an efficient catalyst for the synthesis of sulfur/dinitrogen-fused heterocycles via [3+3] cycloaddition in water

Abstract: The sulfur/dinitrogen-containing heterocycle is an important chemical motif and is found widely in natural products, drug molecules, catalysts and functional materials. Here we report an efficient recoverable amine functionalized mesoporous...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…6 Recently, Zhang and Chen reported an MCM-41-NH 2 -catalyzed [3 + 3] cycloaddition between azomethine imines and 1,4-dioxane-2,5-dithiol in water for the synthesis of sulfur/dinitrogen-fused heterocycles (Scheme 1, eq 5). 7 Up to now, the chemistry of N,N′-cyclic azomethine imines has been limited to the preparation of dinitrogen-fused heterocycles only; that is, the pyrazolidin-3-one skeleton is ubiquitously present in the products. We envision that the development of a strategy for the generation of new molecular scaffolds other than the pyrazolidin-3-one moiety may broaden N,N′-cyclic azomethine imine's application toward the synthesis of structurally diverse heterocycles.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…6 Recently, Zhang and Chen reported an MCM-41-NH 2 -catalyzed [3 + 3] cycloaddition between azomethine imines and 1,4-dioxane-2,5-dithiol in water for the synthesis of sulfur/dinitrogen-fused heterocycles (Scheme 1, eq 5). 7 Up to now, the chemistry of N,N′-cyclic azomethine imines has been limited to the preparation of dinitrogen-fused heterocycles only; that is, the pyrazolidin-3-one skeleton is ubiquitously present in the products. We envision that the development of a strategy for the generation of new molecular scaffolds other than the pyrazolidin-3-one moiety may broaden N,N′-cyclic azomethine imine's application toward the synthesis of structurally diverse heterocycles.…”
mentioning
confidence: 99%
“…Shi et al reported a Brønsted acid-catalyzed [4 + 3] cyclization of azomethine imines with isatoic anhydrides to the preparation of seven-membered nitrogenous heterocycles (Scheme , eq 4) . Recently, Zhang and Chen reported an MCM-41-NH 2 -catalyzed [3 + 3] cycloaddition between azomethine imines and 1,4-dioxane-2,5-dithiol in water for the synthesis of sulfur/dinitrogen-fused heterocycles (Scheme , eq 5) . Up to now, the chemistry of N,N ′-cyclic azomethine imines has been limited to the preparation of dinitrogen-fused heterocycles only; that is, the pyrazolidin-3-one skeleton is ubiquitously present in the products.…”
mentioning
confidence: 99%
See 3 more Smart Citations